Oxidative Damage during the Operation of Si(211)-Based Triboelectric Nanogenerators - Hurtado, Carlos; Ciampi, Simone (2023)
Triboelectric nanogenerators (TENGs) based on sliding metal–semiconductor junctions are an emerging technology that can efficiently convert mechanical into electrical energy. These miniature autonomous power sources can output large direct current (DC) densities, but often suffer from limited durability; hence, their practical scope remains uncertain. Herein, through a combination of conductive atomic force microscopy (C-AFM) and photocurrent decay (PCM) experiments, we explored the underlying cause of surface wear during the operation of DC-TENGs. Using monolayer-functionalized Si(211) surfaces as the model system, we demonstrate the extent to which surface damage develops during TENG operation. We reveal that the introduction of surface defects (oxide growth) during TENG operation is not caused by the passage of the rather large current densities (average output of ~2 × 106 A/m2); it is instead mainly caused by the large pressure (~GPa) required for the sliding Schottky diode to output a measurable zero-bias current. We also discovered that the drop in output during operation occurs with a delay in the friction/pressure event, which partially explains why such deterioration of DC-TENG performance is often underestimated or not reported.